Temperature-ramped 129Xe spin-exchange optical pumping - Nikolaou, Panayiotis; Coffey, Aaron M.; Barlow, Michael J.; Rosen, Matthew S.; Goodson, Boyd M.; Chekmenev, Eduard Y. (American Chemical Society, 2018)
We describe temperature-ramped spin-exchange optical pumping (TR-SEOP) in an automated high-throughput batch-mode 129Xe hyperpolarizer utilizing three key temperature regimes: (i) “hot”where the 129Xe hyperpolarization rate is maximal, (ii) “warm”-where the 129Xe hyperpolarization approaches unity, and (iii) “cool” where hyperpolarized 129Xe gas is transferred into a Tedlar bag with low Rb content (<5 ng per ∼1 L dose) suitable for human imaging applications. Unlike with the conventional approach of batch-mode SEOP, here all three temperature regimes may be operated under continuous high-power (170 W) laser irradiation, and hyperpolarized 129Xe gas is delivered without the need for a cryocollection step. The variable-temperature approach increased the SEOP rate by more than 2-fold compared to the constant-temperature polarization rate (e.g., giving effective values for the exponential buildup constant γSEOP of 62.5 ± 3.7 × 10−3 min−1 vs 29.9 ± 1.2 × 10−3 min−1) while achieving nearly the same maximum %PXe value (88.0 ± 0.8% vs 90.1% ± 0.8%, for a 500 Torr (67 kPa) Xe cell loadingcorresponding to nuclear magnetic resonance/magnetic resonance imaging (NMR/MRI) enhancements of ∼3.1 × 105 and ∼2.32 × 108 at the relevant fields for clinical imaging and HP 129Xe production of 3 T and 4 mT, respectively); moreover, the intercycle “dead” time was also significantly decreased. The higher-throughput TR-SEOP approach can be implemented without sacrificing the level of 129Xe hyperpolarization or the experimental stability for automation-making this approach beneficial for improving the overall 129Xe production rate in clinical settings.